Analysis of Early Childhood Diction Patterns through Spontaneous Storytelling Activities in Preschool Classroom - Mardiah Mardiah; Yulia Warda; Syafrina Prihatini; Armanila Armanila; Friska Anggraini Barus (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Language development in early childhood is a critical phase that requires appropriate stimulation, and diction is an important aspect in the development of children's language skills. This study aims to analyze the diction patterns of early childhood children in spontaneous storytelling activities in early childhood education (PAUD) classes. This study used a qualitative approach with a case study design involving children aged 5-6 years in grade B of PAUD. Data were collected through participant observation, audio-visual recording, and interviews with teachers. The results showed that the diction patterns of early childhood children in spontaneous storytelling have distinctive characteristics that include the use of concrete words, repetition, the influence of the social environment, and the child's cognitive development stage. These findings provide important implications for the development of language learning strategies in PAUD that are more responsive to children's individual needs.